Pengaruh Kombinasi Dekokta Rimpang Jahe Merah (Zingiber officinale) dan Alang-Alang (Imperata cylindrica) Pada Penurunan Kadar Interleukin-1β Serum dan Jumlah Leukosit Tikus Wistar Jantan yang Diinduksi Complete Freund’s Adjuvant - Rahma Auri Wijayanti (Jurnal Kedokteran Komunitas, 2019)
Introduction: Osteoarthritis (OA)  due to predispose and biomechanics factors causing direct degraation of the cartilage. The degradation process causes interleukin-1β (IL-1β) and leukocyte that increases as inflammation sign. The red ginger’s rhizome and cogon grass are known to have anti-inflammatory and antioxidant properties. The herbals were used s a single herb to cure diseases. The present study evaluated the potential of the two herbs for OA treatment by  decrease in IL-1β and leukocyte in rat.Methods: 25 male Wistar rats aged four months, weighed 270-300g were grouped into five groups; negative controls (KN), positive controls (KP), treatment group 1 (P1), treatment group 2 (P2), and treatment group 3 (P3). Four groups of the rats were injected by 0,1ml  right knee intraarticular of  Complete Freund’s Adjuvant (CFA)  to induce OA. Three groups of OA rats are treated with 9+40mg/day (P1), 18+40mg/day (P2), and 36+40mg/day (P3) respectively for 10 days. The treatment of RJMA was conducted 10  days post CFA injection. IL-1β  was measured by IL-1β assay kit and leukocyt were measured hematologyanalyzer. The data were analyzed by One Way Anova test followed by post hoc test. The p < 0.05 was considered to be significant.Results: The given doses of the combination RJMA dereased serum IL-1β and leukocyte compare to positive control (p <0.05). Correlation test between IL-1β levels and leukocytes showed a significant positive (p <0.05). the most effective dose RJMA is 36+40mg/day. The dose approximate that of KN group (p<0,05)Conclusion: The combination of decoction of RJMA at P1, P2, and P3 were able to reduce serum IL-1β and leukocyte count in OA rats caused by CFA induction.Keyword : Osteoarthritis, Decoction Red Ginger’s Rhizome and Cogon Grass, Interlrukin-1β, Leukocyte